A theology of the New Testament - Ladd, George Eldon, 1911-1982. (Grand Rapids, Mich. : Eerdmans, 1993)
Ladd's magisterial work on New Testament theology has well served thousands of seminary students ever since its publication in 1974. Enhanced and updated here by Donald A. Hagner, this comprehensive, standard evangelical text now features augmented bibliographies and two completely new chapters on subjects that Ladd himself wanted to treat in a revised edition--the theology of each of the Synoptic Evangelists and the issue of unity and diversity in the New Testament--written, respectively, by R. T. France and David Wenham.
The Synoptic Gospels -- The fourth Gospel -- The primitive church -- Paul -- Hebrews and the general Epistles -- The Apocalypse.
Includes bibliographical references and indexes.
Keywords: Bible. -- Theology